2000
DOI: 10.1086/315688
|View full text |Cite
|
Sign up to set email alerts
|

New Molecular Assays to Predict Occurrence of Cytomegalovirus Disease in Renal Transplant Recipients

Abstract: Thirty renal transplant recipients, after transplantation, were tested weekly with the following assays: cytomegalovirus (CMV) antigenemia (pp65 Ag), plasma qualitative Amplicor CMV (P-AMP), plasma and peripheral blood leukocyte quantitative Amplicor CMV monitor (P- and PBL-CMM), peripheral blood leukocyte (PBL) quantitative Quantiplex bDNA CMV, version 2.0 (bDNA), and whole-blood Nuclisens pp67 CMV (pp67). Eleven patients developed symptomatic CMV disease, and 7 developed asymptomatic CMV infection. For predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…The use of a more sensitive recombinant antigen ELISA IgM assay (similar to the one used in our study), was found to have some clinical utility in predicting CMV disease in one study of 40 liver transplant recipients, although again DNAemia generally preceded detection of antibody (15). Based on these data, in the past several years, molecular detection methods have generally replaced serology and culture based tests for the diagnosis of active CMV disease (16)(17)(18). There are, however, no previous studies assessing the utility of CMV serology testing in a large cohort of D+/R− patients receiving antiviral prophylaxis, for the purposes of identifying patients at risk of late-onset CMV disease.…”
Section: Discussionmentioning
confidence: 62%
“…The use of a more sensitive recombinant antigen ELISA IgM assay (similar to the one used in our study), was found to have some clinical utility in predicting CMV disease in one study of 40 liver transplant recipients, although again DNAemia generally preceded detection of antibody (15). Based on these data, in the past several years, molecular detection methods have generally replaced serology and culture based tests for the diagnosis of active CMV disease (16)(17)(18). There are, however, no previous studies assessing the utility of CMV serology testing in a large cohort of D+/R− patients receiving antiviral prophylaxis, for the purposes of identifying patients at risk of late-onset CMV disease.…”
Section: Discussionmentioning
confidence: 62%
“…The NucliSens assay (Organon Teknika Diagnostics, Boxtel, The Netherlands), an isothermal nucleic acid amplification reaction assay, detects the presence of CMV latemRNA pp67. The presence of mRNA pp67 indicates active viral replication, and its detection is a marker for active CMV infection (18,19). Nevertheless, this assay has less sensitivity than DNA amplification and antigenemia assays for detection of CMV infection.…”
mentioning
confidence: 99%
“…The lower sensitivity of the assay may result in failure to detect or predict CMV disease in all patients (22). In one study, the assay did not detect the mRNA transcripts in 4 of 11 patients who developed CMV disease (19). A commercially available COBAS Amplicor CMV Monitor (CACM) assay has been developed by Roche Diagnostics (Branchburg, N.J.) for the determination of CMV DNA load (5,6,30).…”
mentioning
confidence: 99%
“…For the benefit of such strategies, quantitative detection of CMV DNA in the blood compartment by PCR is increasingly used to identify patients at risk for CMV disease. In addition, measurements of viral DNA load may be important for monitoring the efficacy of antiviral treatment and predicting the development of drug resistance (3,22,27).The genome of human CMV consists of a large (about 230,000-bp) double-stranded linear DNA molecule which is encapsidated within a double protein shell and a lipid envelope (24). Most of the CMV DNA in the blood compartment is present in abortively infected polymorphonuclear leukocytes (4,12,16,26); less DNA is found in peripheral blood mononuclear cells, part of which, upon differentiation into macrophages, support viral replication (12,26,28).…”
mentioning
confidence: 99%
“…For the benefit of such strategies, quantitative detection of CMV DNA in the blood compartment by PCR is increasingly used to identify patients at risk for CMV disease. In addition, measurements of viral DNA load may be important for monitoring the efficacy of antiviral treatment and predicting the development of drug resistance (3,22,27).…”
mentioning
confidence: 99%